The Design of Nonuniform Lapped Transforms - Yoon, Byung-Jun; Malvar, Henrique S. (2005)
We propose a new method for designing nonuniform lapped transforms. The proposed method provides a simple yet effective way of designing lapped transforms with nonuniform frequency resolution and good time localization. This method is a generalization of an approach proposed by Princen, where the non-uniform filter bank is obtained by joining uniform cosine-modulated filter banks using transition filters. In the proposed approach, we use several transition filters to obtain a near perfect-reconstruction nonuniform lapped transform with significantly reduced overall distortion. This method has several advantages over existing ones, especially in producing nonuniform filter banks with good stopband attenuation and short filters; the resulting reduced delay makes the proposed method preferable for applications such as real-time audio coding.